2008
DOI: 10.1007/s11103-007-9277-1
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a 236 kb region around S 4-RNase in a stylar-part mutant S 4 sm -haplotype of Japanese pear

Abstract: Japanese pear (Pyrus pyrifolia Nakai) has a gametophytic self-incompatibility (GSI) mechanism controlled by a single S-locus with multiple S-haplotypes, each of which contains separate genes that determine the allelic identity of pistil and pollen. The pistil S gene is the S-ribonuclease (S-RNase) gene, whereas good candidates for the pollen S gene are the F-box protein genes. A self-compatible (SC) cultivar, 'Osa-Nijisseiki', which is a bud mutant of 'Nijisseiki' (S (2) S (4)), has a stylar-part mutant S(4)sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
86
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 32 publications
1
86
0
Order By: Relevance
“…For example, the S 4 -RNase gene in Japanese pears (Pyrus pyrifolia) is lost in the genome of cv. Osa-Nijisseiki (Okada et al 2008), while the S 21 -RNase gene in European pears (Pyrus communis) is not expressed in the pistil of cv. Abugo (Sanzol 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, the S 4 -RNase gene in Japanese pears (Pyrus pyrifolia) is lost in the genome of cv. Osa-Nijisseiki (Okada et al 2008), while the S 21 -RNase gene in European pears (Pyrus communis) is not expressed in the pistil of cv. Abugo (Sanzol 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Most fruit tree species in the subfamilies Prunoideae and Maloideae exhibit self-incompatibility, and only a few genotypes are self-compatible . In Maloideae, it has been reported that loss of selfincompatibility may result from stylar-part mutation (SPM) (Okada et al 2008). For example, the S 4 -RNase gene in Japanese pears (Pyrus pyrifolia) is lost in the genome of cv.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations